Pengintegrasian Nilai-Nilai ke-Islaman dengan Pembelajaran Bahasa Jawa - Farizal, Muhamad; Muqowim, Muqowim (STAI Auliaurrasyidin Tembilahan, 2021)
The purpose of this study was to determine the process and the integration of Islamic values ​​into Javanese language learning. This research method was carried out qualitatively descriptive. This study described how the teacher combines Islamic values ​​with Javanese language learning for grade V students. The subjects of this study were students and teachers of MI Ma'arif Darussalam. The data collection technique used was unstructured interviews. Observations are made by observing teacher activities in the classroom and outside the classroom in teaching activities that are familiar with the student's personality. Documentation was done by finding and collecting documents related to the teaching plan to get data about the habits of these characters. Data analysis techniques using data reduction, data display, and conclusions. The result of this research is that the integration of Islamic values ​​with Javanese language learning carried out by the teacher is already at a good stage and has been implemented in the Madrasah Ibtidaiyah